1994
DOI: 10.1136/bjo.78.9.698
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral retinoblastoma: new intraocular tumours after treatment.

Abstract: (Br3r Ophthalmol 1994; 78: 698-701)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 12 publications
2
16
0
Order By: Relevance
“…Our findings are in keeping with those reported by Abramson et al 18 and Wilson et al ,19 who found family history and young age of presentation to be associated with increased risk of developing new tumours. Interestingly, eight (15%) of the unilateral patients in the present study (not including the abovementioned one) were found to be genetic cases; however, these too remained unilateral throughout follow-up.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are in keeping with those reported by Abramson et al 18 and Wilson et al ,19 who found family history and young age of presentation to be associated with increased risk of developing new tumours. Interestingly, eight (15%) of the unilateral patients in the present study (not including the abovementioned one) were found to be genetic cases; however, these too remained unilateral throughout follow-up.…”
Section: Discussionsupporting
confidence: 93%
“…In developing countries, where family incomes are modest and access to care is limited, early enucleation for advanced intraocular unilateral retinoblastoma is to be recommended. However, a case for eye preservation can be made for patients who present with unilateral retinoblastoma before 6 months of age, because the possibility of asynchronous retinoblastoma is a significant concern [12].…”
Section: Discussionmentioning
confidence: 99%
“…About 4% of children with an initial diagnosis of unilateral retinoblastoma develop new intraocular tumour foci in the other eye (metachronous bilateral tumours) after treatment 2. To assure early detection and treatment of the few patients who develop new tumour foci, repeated follow-up eye examinations under anaesthesia are recommended for all patients with unilateral retinoblastoma until 5 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…To assure early detection and treatment of the few patients who develop new tumour foci, repeated follow-up eye examinations under anaesthesia are recommended for all patients with unilateral retinoblastoma until 5 years of age. Studies undertaken to this end so far have shown that early age at initial diagnosis and initial diagnosis of multifocal tumours are associated with a higher than average risk 2 3. The strongest risk factor for development of metachronous bilateral tumours is a positive family history of retinoblastoma.…”
Section: Introductionmentioning
confidence: 99%